Studi Kualitatif Sosialisasi Dan Komunikasi Program Layanan Internet Kecamatan Melalui FGD Dalam Pemberdayaan Masyarakat Di Provinsi Bengkulu - Abubakar Iskandar (Institut Pertanian Bogor, 2011)
ABSTRACT Socialization qualitatif study and communication program of rural internet services through focus discussion group for community development in provinci of Bengkulu. The aims of this research was: To determine the extent of coordination and cross-level communication (Bappeda, Dinas Kominfo, Dinas Kesehatan, Dinas Pendidikan, Dinas Koperasi dan Usaha Kecil Menengah, Dinas Perhubungan, Perguruan Tinggi dan Tokoh masyarakat) in optimizing the program of internet services district (PLIK). The research design was qualitative descriptive. A sample of this research using two or more cluster gradually. Collected data are primary and secondary data. Techniques used in this research were interviews, focus group discussion, observation and documentation. Data analysis in this research was a qualitative analysis. Qualitative analysis reached by applying content analysis techniques. The result showed that: (1) The lack of socialization and cross-level communication about PLIK (internet service district program); (2) Performance of provincial coordinators, facilitators, and manager was not optimal in optimizing PLIK; (3) The persistence of corruption and the status of several computer devices “off” and (4) Socialization, communication, and a good IT training can be to the participants, advocates in the province of Bengkulu, if in accordance with the concept that has been selected by expert team. Key words: coordination, communication, internet, community development